German and Indonesian Politeness Strategies: A Contrastive Study and Its Pedagogical Implications for German Language Teaching - Ending Khoerudin; Putrasulung Baginda; Dani Hendra (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2026)
This study investigates politeness strategies represented in the German textbook Netzwerk A1 and contrasts them with documented Indonesian politeness norms to explore their pedagogical implications for German language teaching in Indonesia. Grounded in contemporary politeness theory and contrastive pragmatics, the research employs a qualitative descriptive design based on systematic document analysis. Dialogic interactions in the textbook were examined to identify patterns of directness, grammatical mitigation, hierarchical encoding, lexical politeness markers, and the use of Konjunktiv II. A micro-contrastive analysis of representative request forms further illustrates divergences between German structurally direct but grammatically mitigated formulations and Indonesian relationally oriented, lexically mediated politeness strategies. Interpreted through the distinction between pragmalinguistic and sociopragmatic dimensions, the findings reveal that differences extend beyond linguistic structure to culturally grounded evaluations of appropriateness and hierarchy. These divergences highlight potential areas of pragmatic transfer among Indonesian learners of German. This study contributes to the field of pragmatics by expanding contrastive analysis beyond English-centered paradigms and by providing a multi-layered account of politeness that integrates structural, lexical, and grammatical dimensions. The findings also offer pedagogical insights for developing intercultural pragmatic competence in German language teaching.